The screening potentials of ion-dipole system adsorbed in ion-dipolar disordered matrices - Holovko, M.F.; Polishchuk, Z.V. (Condensed Matter Physics, 1999)
The replica Ornstein-Zernike equations ion-molecular ﬂuid adsorbed in a
disordered ion-molecular matrix were applied. The explicit expressions for
the potentials screening by the point particles are obtained. The analysis
of the screening potentials for ion-dipolar case are presented. It is shown
that ﬂuid-ﬂuid interionic potentials include connected and blocked parts. Розглядається метод репліки для рівнянь Орнштейна-Церніке для
іонно-молекулярної рідини, адсорбованої в невпорядкованій іонно-молекулярній матриці. Отримано явні вирази для екранованих потенціалів для іонно-дипольного випадку. Показано, що флюїд-флюїд міжіонний потенціал розкладається на зв’язуючу і блоковану
частини.